1981
DOI: 10.1007/bf01542671
|View full text |Cite
|
Sign up to set email alerts
|

Physical attractiveness: The influence of selected torso parameters

Abstract: Front-view line drawings of male and female physiques were rated for attractiveness. Both subject sexes rated female physiques with greater curvature as less attractive. Male subjects' ratings were unaffected by breast size while female subjects showed slight negative evaluation of large breasts. Both subjects sexes rated broad shoulders as attractive in male physiques. Greater chest muscularity resulted in slightly higher attractiveness ratings; waist slimness was also judged attractive, particularly in femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
2

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 5 publications
2
35
0
2
Order By: Relevance
“…Studies of male preferences for female breast size have produced mixed results. Some studies have found that men rate line drawings of women with medium sized breasts as most attractive (Horvath, 1981;Wiggins, Wiggins, & Conger, 1968) while other studies have found that men prefer smaller breasts (Furnham, Swami, & Shah, 2006) or larger breasts (Singh & Young, 1995). The mixed responses from men reported in these studies suggest that further investigations of female breast size and sexual attractiveness would be valuable.…”
Section: Introductionmentioning
confidence: 84%
“…Studies of male preferences for female breast size have produced mixed results. Some studies have found that men rate line drawings of women with medium sized breasts as most attractive (Horvath, 1981;Wiggins, Wiggins, & Conger, 1968) while other studies have found that men prefer smaller breasts (Furnham, Swami, & Shah, 2006) or larger breasts (Singh & Young, 1995). The mixed responses from men reported in these studies suggest that further investigations of female breast size and sexual attractiveness would be valuable.…”
Section: Introductionmentioning
confidence: 84%
“…In particular, as several studies have shown that broad shoulders contribute to perceptions of male attractiveness (e.g. Franzoi & Herzog, 1987;Horvath, 1981;Lavrakas, 1975;Lippa, 1983) and that males become jealous particularly when their rival has broad shoulders , also the characteristic 'broader shoulders' was included as a further specification of the characteristics 'better figure/body build' (for men), 'strength' and 'muscular'. In a similar vein, because both waist and hips strongly influence bodily attractiveness for women (Franzoi & Herzog, 1987;Horvath, 1981;Singh, 1993;Tassinary & Hansen, 1998), and because females become particularly jealous when their rival has a low waist-to-hip ratio , both these characteristics were included (as a specification of 'better figure' and slenderness for female participants).…”
Section: Studymentioning
confidence: 99%
“…Franzoi & Herzog, 1987;Horvath, 1981;Lavrakas, 1975;Lippa, 1983) and that males become jealous particularly when their rival has broad shoulders , also the characteristic 'broader shoulders' was included as a further specification of the characteristics 'better figure/body build' (for men), 'strength' and 'muscular'. In a similar vein, because both waist and hips strongly influence bodily attractiveness for women (Franzoi & Herzog, 1987;Horvath, 1981;Singh, 1993;Tassinary & Hansen, 1998), and because females become particularly jealous when their rival has a low waist-to-hip ratio , both these characteristics were included (as a specification of 'better figure' and slenderness for female participants). Likewise, as research suggests that a light body build contributes heavily to female mate value whereas a heavy body build contributes to male attractiveness (Cohn et al, 1987;Fallon & Rozin, 1985), the characteristics 'is built lighter' (also as a specification of 'better figure' and slenderness for female participants), and 'is built heavier' were included (related to 'muscularity' and 'better body build' for male participants).…”
Section: Studymentioning
confidence: 99%
“…However, findings on the relationship between breast size and attractiveness are inconsistent; some studies have found that men rate line drawings of women with average-sized breasts as most attractive (Horvath, 1981;Wiggins, Wiggins, & Conger, 1968), while other studies have concluded that men prefer smaller breasts (Furnham, Swami, & Shah, 2006) or larger breasts (Singh & Young, 1995).…”
Section: Introductionmentioning
confidence: 95%